1979
DOI: 10.3382/ps.0580852
|View full text |Cite
|
Sign up to set email alerts
|

Replacing Corn with Sun-Dried Manure of Laying Pullet, Mature Pig, Sheep, and Cow

Abstract: Sun dried (30 to 35 C) manure of adult fowl, pig, cow, or sheep was used to replace 5, 10, 15, and 20% of the maize in corn-peanut base diets for started broiler and pullet replacement chicks and for laying pullets. The manure of the fowl followed by that of the cow were superior to that of pig and of sheep in replacing up to 15% of maize (7.5% of the whole diet) for the different categories of birds used in the experiment. The beneficial effects of the poultry and cow manure were manifested most prominently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
2
1
0
Order By: Relevance
“…However, the better results that appeared when diets were supplemented with Kemzyme might be due to the presence of Alfa-amylase, Beta-glucanase, Protease, Lipase, Cellulase and Bentonite enzymes in KZ, which helped in improving the utilization of diets contain manures. The present finding are in good agreement with those of Lipestein and Bortein (1973); Oluyemi et al (1979), Ahmed, (1981; Abdel-Hakim et al (1991) and Soliman (1992) for CM, Flegal andZindal (1971 &; Biely et al (1972);Trakulchange and Balloun, (1975); Galal et al (1977); Hassan, (1984); Abdel-Moty et al (1986); Abdel-Hakim et al (1991) and El-Hussieny et al (1994) for PM and Chawan et al (1979); Elemele et al (1980), Mendonca et al (1980); Malavazzi et al (1985) and Abdel-Hakim et al (1991) for RM. They found that the best results of hen performance were found when manures were used at levels of 10 -15 % of laying hen diets.…”
Section: Laying Hen Performancesupporting
confidence: 94%
See 2 more Smart Citations
“…However, the better results that appeared when diets were supplemented with Kemzyme might be due to the presence of Alfa-amylase, Beta-glucanase, Protease, Lipase, Cellulase and Bentonite enzymes in KZ, which helped in improving the utilization of diets contain manures. The present finding are in good agreement with those of Lipestein and Bortein (1973); Oluyemi et al (1979), Ahmed, (1981; Abdel-Hakim et al (1991) and Soliman (1992) for CM, Flegal andZindal (1971 &; Biely et al (1972);Trakulchange and Balloun, (1975); Galal et al (1977); Hassan, (1984); Abdel-Moty et al (1986); Abdel-Hakim et al (1991) and El-Hussieny et al (1994) for PM and Chawan et al (1979); Elemele et al (1980), Mendonca et al (1980); Malavazzi et al (1985) and Abdel-Hakim et al (1991) for RM. They found that the best results of hen performance were found when manures were used at levels of 10 -15 % of laying hen diets.…”
Section: Laying Hen Performancesupporting
confidence: 94%
“…This might be due to the presence of some pigment substances in MM such as xanthophylls. This result is in agreement with those of Oluyemi et al (1979), Ahmed (1981) and Soliman (1992). Concerning ST, except the group of T6, no significant differences were found among all dietary treatments.…”
Section: Egg Qualitysupporting
confidence: 93%
See 1 more Smart Citation